Pengembangan Kurikulum Kewirausahaan di Sekolah Dasar - Hasibuan, Budi Azhari Muda; Siregar, Royhanun (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of writing this article is to examine the development of the entrepreneurship curriculum in elementary schools. The aspects studied are the definition of the entrepreneurship curriculum, the foundation for the development of the entrepreneurship curriculum, and the model and value of entrepreneurship in elementary schools. The research method used is a literature study study. The documents studied in this study are books and articles with national reputation. Documents are collected, analyzed, and concluded through scientific studies. The results of this study show that the entrepreneurship curriculum is very important to be developed for the advancement of the independence of the Indonesian people. The development of an entrepreneurship curriculum at the elementary school level is considered very appropriate to develop this curriculum as early as possible. Because at this stage of development, elementary school students already have the ability to think and be creative, which is enough, so it is very easy to guide them to absorb and implement entrepreneurial values in their learning experience. It is hoped that elementary school students will be able to create innovations that will later produce valuable products, so that through the products produced indirectly it will instill an entrepreneurial spirit and entrepreneurial mentality in students